Property rights, planning and markets : managing spontaneous cities - Webster, Christopher J.; Lai, Lawrence Wai-chung (Cheltenham, UK ; Northhampton, MA : Edward Elgar Pub., 2003)
The book in effect offers a positive theory of planning and urbanisation
Includes bibliographical references (p. 220-228) and index
rua 25/09/14
Loans
Keywords: City planning; Markets; Right of property; Planning